Effects of shift work on 24-hour ambulatory blood pressure and its variability among Japanese workers - Ohira, T; Tanigawa, T; Iso, H; Odagiri, Yuko; Takamiya, T; Shimomitsu, T; Hayano, Junichiro; Shimamoto, T (Scandinavian Journal of Work, Environment & Health, 2000)
' ' OBJECTIVES ': 'This study examined the effects of rotating shift work on blood pressure in a comparison of ambulatory blood pressure and long-term changes in blood pressure between shift and day workers.' ' METHODS ': 'Ambulatory blood pressure was measured for 24-hour periods at an interval of 30 minutes for 27 shift workers and 26 day workers when they worked during the day. Blood pressure was compared between these 2 groups of workers for 4 time categories (awake, sleep, nonwork awake, and work periods). Their long-term blood pressures, recorded in annual surveys, were reviewed for long-term changes. These comparisons were adjusted for the effects of body mass index, alcohol intake, anger expression, and physical activity.' ' RESULTS ': 'On the average, sleep time was shorter and the anger-in (ie, anger suppressed) score was higher for the shift workers than for the day workers, but body mass index and alcohol intake did not differ between the 2 groups. Even after adjustment for these co-variables, the mean systolic blood pressure during the 24-hour, awake, and work periods were higher among the shift workers than among the day workers. The 24-hour standard deviations of the systolic blood pressures were also higher for the shift workers than for the day workers. Among the shift workers, but not among the day workers, a significant long-term increase was observed in systolic blood pressure measured in the annual surveys.' ' CONCLUSIONS ': 'These results suggest that shift work may increase systolic blood pressure levels among Japanese men.
Keywords: anger expression; blood pressure monitoring; circadian rhythm; shift worker; sleep